Examination of Curriculum of Azerbaijan in Terms of Citizenship Training - (:unkn) unknown (MARMARA UNIV, 2018)
The primary aim of this study is to examine the elementary, primary and high school citizenship education curricula that was approved and started to be implemented in 2006. The study was designed and conducted in accordance with the qualitative research method, and the data that were gathered through document analysis were analysed by means of descriptive analysis technique. The overall objectives and courses in the curricula concerned were examined, and it was aimed to demonstrate how citizenship education is delivered in the Republic of Azerbaijan. In this regard, the analysis focused on the question of what characteristics an ideal citizen should have as prescribed in the curricula. Based on the findings revealed in the study, it can be asserted that citizenship education in Azerbaijani elementary, primary and high schools is shaped mainly on first language education, life skills, Azerbaijani history, and military information. It is possible to describe the ideal citizen as referred to in the country's educational curricula as an individual who has at least the basic technological skills required by the age of technology in the 21st century, is equipped with skills necessary for individual and social development, particularly thinking skills, can speak at least one foreign language in daily life, and internalises national cultural elements as well as transfers them into his/her life. In the context of citizenship education, the educational curricula under examination were balanced in terms of the national/universal dichotomy/relationship, and have the objective of equipping citizens with national cultural elements while also aiming to teach them universal knowledge, skills and values.
Keywords: Citizenship Education; Azerbaijan; Educational Curricula; Nation Building